Comparison of In Vitro Hair Growth Promotion and Anti-Hair Loss Potential of Thai Rice By-Product from Oryza sativa L. cv. Buebang 3 CMU and Sanpatong - Anurak Muangsanguan; Warintorn Ruksiriwanich; Chaiwat Arjin; Sansanee Jamjod; Chanakan Prom-u-Thai; Pensak Jantrawut; Pornchai Rachtanapun; Patipan Hnorkaew; Apinya Satsook; Mathukorn Sainakham; Juan Manuel Castagnini; Korawan Sringarm (Plants)
The bioactive compounds in herbal extracts may provide effective hair loss treatments with fewer side effects compared to synthetic medicines. This study evaluated the effects of Buebang 3 CMU and Sanpatong rice bran extracts, macerated with dichloromethane or 95% ethanol, on hair growth promotion and hair loss prevention. Overall, Buebang 3 CMU extracts contained significantly higher levels of bioactive compounds, including γ-oryzanol, tocopherols, and various polyphenols such as phytic acid, ferulic acid, and chlorogenic acid, compared to Sanpatong extracts. Additionally, ethanolic extracts demonstrated greater bioactive content and antioxidant activities than those extracted with dichloromethane. These compounds enhanced the proliferation of human hair follicle dermal papilla cells (HFDPCs) by 124.28 ± 1.08% (p < 0.05) and modulated anti-inflammatory pathways by reducing nitrite production to 3.20 ± 0.36 µM (p < 0.05). Key hair growth signaling pathways, including Wnt/β-catenin (CTNNB1), Sonic Hedgehog (SHH, SMO, GLI1), and vascular endothelial growth factor (VEGF), were activated by approximately 1.5-fold to 2.5-fold compared to minoxidil. Also, in both human prostate cancer (DU-145) and HFDPC cells, the ethanolic Buebang 3 CMU extract (Et-BB3-CMU) suppressed SRD5A1, SRD5A2, and SRD5A3 expression—key pathways in hair loss—by 2-fold and 1.5-fold more than minoxidil and finasteride, respectively. These findings suggest that Et-BB3-CMU holds promise for promoting hair growth and preventing hair loss.